Randomized clinical trial of sacral nerve stimulation for refractory constipation. Issue 3 (25th October 2016) - Zerbib, F; Siproudhis, L; Lehur, P-A; Germain, C; Mion, F; Leroi, A-M; Coffin, B; Le Sidaner, A; Vitton, V; Bouyssou-Cellier, C; Chene, G; Zerbib, F; et al.
Abstract: Background: Open studies have reported favourable results for sacral nerve stimulation in the treatment of refractory constipation. Here, its efficacy was assessed in a double-blind crossover RCT. Methods: Patients with at least two of the following criteria were included: fewer than three bowel movements per week; straining to evacuate on more than 25 per cent of attempts; or sensation of incomplete evacuation on more than 25 per cent of occasions. Response to therapy was defined as at least three bowel movements per week and/or more than 50 per cent improvement in symptoms. Responders to an initial 3-week peripheral nerve evaluation were offered permanent implantation of a pulse generator and were assigned randomly in a crossover design to two 8-week intervals of active or sham stimulation. At the end of the two trial periods, the patients received active stimulation until the final evaluation at 1 year. Results: Thirty-six patients (34 women; mean(s.d.) age 45(14) years) underwent peripheral nerve evaluation. Twenty responded and received a permanent stimulator. A positive response was observed in 12 of 20 and 11 of 20 patients after active and sham stimulation periods respectively ( P = 0·746). Pain related to the device occurred in five patients and wound infection or haematoma in three, leading to definitive removal of the pulse generator in two patients. At 1 year, 11 of the 20 patients with an implanted device continued to respond. Stimulation had no significant effect on colonic transit time. Conclusion: These results do not support the recommendation of permanent implantation of a pulse generator in patients with refractory constipation who initially responded to temporary nerve stimulation. Registration number: NCT01629303 (http://www.clinicaltrials.gov ). Abstract : Limited value in constipation